Impacts of lightning-induced overvoltage on a hybrid solar PVbattery energy storage system - Ahmad N.I.; Ali Z.; Kadir M.Z.A.A.; Osman M.; Zaini N.H.; Roslan M.H. (MDPI AG, 2023)
With increased electrical energy demands projected in the future, the development of a hybrid solar photovoltaic (PV)battery energy storage system is considered a good option. However, since such systems are normally installed outdoors and in open areas, they are vulnerable to lightning strikes and may suffer from malfunctions or significant damage to sensitive components, which may result in a major breakdown and loss of revenue due to equipment replacement costs and inefficient operation. Thus, the objective of this paper is to investigate the effect of lightning-induced overvoltage on a hybrid solar PVbattery energy storage system, considering indirect lightning strikes nearby the system. The presented hybrid solar PVbattery energy storage system and lightning-induced overvoltage are modeled in Electro-Magnetic Transient Program-Restructured Version (EMTP-RV) software. The lightning-induced overvoltage is simulated based on a lightning waveshape of 10/350 s using the Heidler expression, whilst the Rusck model is used to simulate the lightning-induced overvoltage. Different lightning current amplitudes (3, 19, and 169 kA), lightning strike locations (20, 50, and 100 m), and cable lengths (5, 10, and 20 m) are used to investigate the induced effects on the system and on the impulse withstand voltage of 6kV, as stated in MS IEC 60664-1 for solar PVbattery systems and inverters at the DC side. The results indicate that as the lightning strike distance increases from 20 to 100 m, the percentage of strikes exceeding the impulse withstand voltage reduces from 67% to 54% at 19 kA. At 169 kA, the impulse withstand voltage is exceeded by more than 100%, regardless of the strike distance (from 20 to 100 m). Furthermore, differences in cable length do not have much impact on the lightning-induced overvoltage due to the small voltage drop across the short cable length. This study provides useful information for PV systems owners and will be useful in assigning appropriate lightning protection schemes for PV farms. 2021 by the authors. Licensee MDPI, Basel, Switzerland.